JEDEDIAH PURDY - After Nature: A Politics of the Anthropocene (ZARCH, 2021)
Jedediah PurdyAfter Nature: A Politics of the AnthropoceneCambridge, Massachusetts: Harvard University Press, 2015. 336 p. Idioma: inglés.Tapa dura. 31,50 €ISBN: 9780674368224